Method for assessing unevenness of cellulose insulation layers aging of power transformers winding - Poliakov, M. O.; Vasylevskyi, V. V. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2022)
Introduction. Improving the methods of estimating the insulation aging of the oil-immersed power transformer windings is an urgent task for transformer condition monitoring systems. The scientific novelty of the work is to take into account the uneven distribution of temperature and humidity along the vertical axis of the winding in modeling the aging of insulation and to develop methods for determining the conditions under which the aging rate of insulation in the intermediate layer will exceed aging rate in the hottest layer. The purpose of the work is to evaluate the wear unevenness of cellulose insulation based on modeling the distribution of temperature and humidity along the vertical axis of the power transformer winding. Methods. The transformer winding is mentally divided into horizontal layers of equal height, the reduction of service life is calculated in parallel for all horizontal layers. Layer with the maximum degree of aging for the entire period of operation and storage of the transformer is recognized as determining the reduction in the service life of the insulation of the transformer as a whole. A model of the interaction of winding layers is developed, with determination of temperatures, humidity, relative rate of aging of each layer due to temperature and humidity as a function of traditional design parameters such as load, cooling temperature, heat capacity and thermal resistance of transformer. The index of exceeding the aging rate by the layered method in comparison with this rate for the hottest layer is offered. The method of genetic algorithms determines the conditions for obtaining the maximum value of this index. Results. A computer model has been developed to predict the aging of the cellulose insulation of transformer windings. According to the proposed method, a layer with significantly shorter insulation aging time (in the example, time reduced by 39.18 %) than for the upper layer was determined, which confirms the feasibility of layer-by-layer monitoring and modeling of insulation aging processes of power oil-immersed transformer windings.